THE PATTERN OF ORGANOPHOSPHORUS COMPOUNDS POISONING AT A TERTIARY CARE TEACHING HOSPITAL AND MEDICAL COLLEGE IN NORTHERN INDIA - KANIKA KOHLI; RANJODH JEET SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: A retrospective study was conducted in a tertiary care hospital collaborated with a medical college, to analyze the drug therapy including antidotes administered and pattern of Organophosphorous compounds poisoning. Material and methods: The data are analytically drawn from record sheets of Organophosphorous poisoning patients. The collected tabulated data were statistically analyzed with SPSS version for the pattern of Organophosphorous compounds poisoning. Results: The demographic data of 122 Organophosphorous poisoning clinical cases documented 84.42 % suicidal tendency and 15.57 % accidental exposure of patients, 66.39 % in the age of 15-24 years, and 70.49 % were females and 70.49 % from a rural background, and 29.50 % from an urban background. Before pharmacotherapy, all patients were subjected to general supportive measures including stomach wash, and patients were administered pharmacotherapy consisting of Pralidoxime (23.77 %) and Atropine (41.80 %). Conclusion: This present concluded that patients diagnosed with Organophosphorous poisoning can be managed by alone administration of atropine as an antidote which is available as a cost-effective drug as compared to Pralidoxime. Thus cost-effectiveness can be significantly reduced by the rational drug use and strict implementation of the pesticide act to further strengthen the proper maintenance of procurement of Organophosphorous compounds for exclusive agricultural purpose.